Modernization of tax control in the context of digitalization of the economy - E. A. Kirova (Publishing House of the State University of Management, 2020)
Actual problems of modernization of tax control have been considered and proposals aimed at the development of tax administration in the context of digitalization of the economy have been formed. The risks of using big data in the tax sphere have been determined, the conclusion about the need for state regulation of the use of Big Data technology has been made. The purpose of the article is to substantiate the key areas of tax control modernization through the use of modern digital technologies, as well as to develop practical proposals for their implementation. Methods of system approach, analysis and synthesis, as well as abstraction and generalization have been used. It has been concluded about the need to develop legislation in the field of digitalization of the economy, state regulation of the use of big data technology, ensuring reliable database security and protection ofprivacy, as well as the creation of software for identifying transactions.